2016
DOI: 10.32607/20758251-2016-8-1-82-89
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism Underlying the Action of Substituted Pro-Gly Dipeptide Noopept

Abstract: This study was performed in order to reveal the effect of Noopept (ethyl ester of N-phenylacetyl-Lprolylglycine, GVS-111) on the DNA-binding activity of transcriptional factors (TF) in HEK293 cells transiently transfected with luciferase reporter constructs containing sequences for CREB, NFAT, NF-κB, p53, STAT1, GAS, VDR, HSF1, and HIF-1. Noopept (10 μM) was shown to increase the DNA-binding activity of HIF-1 only, while lacking the ability to affect that of CREB, NFAT, NF-κB, p53, STAT1, GAS, VDR, and HSF1. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For example, in the above-mentioned review [30], the description of the mechanism of the biological effects of peptides only touches on their ability to regulate gene expression. At the same time, as it was mentioned earlier, gene expression may be regulated by different mechanisms, DNA methylation, and/or histone acetylation, as well as transcription factors [27]. In the following, the authors will explore the mechanisms of peptide interaction with DNA and histones to explain the specificity of peptides' biological action.…”
Section: Interaction Of Short Peptides With Dna and Histone Proteinsmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, in the above-mentioned review [30], the description of the mechanism of the biological effects of peptides only touches on their ability to regulate gene expression. At the same time, as it was mentioned earlier, gene expression may be regulated by different mechanisms, DNA methylation, and/or histone acetylation, as well as transcription factors [27]. In the following, the authors will explore the mechanisms of peptide interaction with DNA and histones to explain the specificity of peptides' biological action.…”
Section: Interaction Of Short Peptides With Dna and Histone Proteinsmentioning
confidence: 94%
“…There are very few studies in this area as compared, for example, to the considerable data available on the DNA methylation and/or histone acetylation, peptide binding with transcription factors, etc. [27]. However, studies of the patterns of DNA-peptide interactions identified in vitro help to characterize the specificity of action of short peptides.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Pro-Gly significantly enhanced elastin synthesis of normal human dermal fibroblasts (NHDF) without affecting the rate of cell proliferation ( 32 ). Furthermore, Noopept (ethyl ester of N-phenylacetyl-L-prolylglycine), Pro-Gly-containing dipeptide, increased the DNA-binding activity of hypoxia-inducible factor 1 (HIF-1) in HEK293 cells ( 33 ). These results suggested the bioactive effects of the dipeptide Pro-Gly.…”
Section: Introductionmentioning
confidence: 99%